Reactions with Antisera and Pathological Effects of Staphylococcus aureus Gamma-Toxin in the Cornea. (3rd August 2017) - Bierdeman, Michael A.; Torres, Angela M.; Caballero, Armando R.; Tang, Aihua; O'Callaghan, Richard J.
ABSTRACT: Purpose : This study analyzed the toxicity of purified gamma-toxin from Staphylococcus aureus and the protectiveness of antisera to gamma-toxin in the rabbit cornea. Materials and methods : Gamma-toxin was purified from cultures of alpha-toxin deficient S. aureus strain Newman Δhla . Antisera to native gamma-toxin (Hlg) were produced in rabbits. These antisera and a commercial polyclonal antibody to recombinant HlgB (rHlgB) were analyzed for specificity and toxin neutralization. Heat-inactivated gamma-toxin, active gamma-toxin either alone or with antisera or with commercial antibody to rHlgB, was injected into the rabbit cornea to observe the pathological effects using slit lamp examination scoring (SLE) and histological analyses. Results : Eyes with intrastromal injection of gamma-toxin developed SLE scores that were significantly higher than eyes injected with heat-inactivated gamma-toxin ( p ≤ 0.003). Slit lamp and histological examination of eyes revealed that gamma-toxin injected into the cornea mediated conjunctival injection and chemosis, iritis, fibrin accumulation in the anterior chamber, and polymorphonuclear neutrophil infiltration of the cornea and iris. Also, eyes injected with gamma-toxin plus antisera to native whole gamma-toxin or HlgB, but not with commercial antibody to rHlgB, yielded significantly lower SLE scores than eyes injected with gamma-toxin alone ( p ≤ 0.003). Conclusions : This study illustrates that S. aureus gamma-toxin is capable of causing significant corneal pathology. Furthermore, the use of polyclonal antisera specific for native gamma-toxin was found to inhibit the damaging effects of the toxin in the rabbit cornea.